Cars [videorecording (DVD)] - Lasseter, John; Wilson, Owen, 1968-; Newman, Paul, 1925-2008; Hunt, Bonnie (Walt Disney Home Entertainment : Distributed by Buena Vista Home Entertainment, 2006)
Hotshot rookie race car Lightning McQueen is living life in the fast lane until he hits a detour on his way to the most important race of his life. Stranded in Radiator Springs, a forgotten town on old Route 66, he meets Sally, Mater, Doc Hudson, and a variety of quirky characters who help him discover that there's more to life than trophies and fame.